Relationships between eccentric and concentric knee strength capacities and maximal linear deceleration ability in male academy soccer players - Harper, D. J.; Jordan, A. R.; Kiely, J. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to investigate the relationships between maximal linear deceleration ability, and knee flexor (KF) and knee extensor (KE) strength. Fourteen male academy soccer players completed a 30-m linear sprint, a maximal linear deceleration test, and eccentric and concentric KF and KE contractions in both dominant leg (DL) and nondominant leg (NDL) at slower (60°/s) and faster (180°/s) angular velocities on an isokinetic dynamometer. Maximal linear deceleration ability was evaluated using distance-to-stop (DEC-DTS) and time-to-stop (DEC-TTS), with isokinetic peak torque representing KF and KE strength capacity. Relationships were established using Pearson's correlation coefficients (r) with magnitude-based inferences used to describe the uncertainty in the correlation. Both concentric KE and KF strength at 180°/s in the NDL had the highest correlations with deceleration ability (r = -0.76 and r = -0.78, respectively). In the DL, concentric KE and KF strength at 180°/s also had very likely large correlations with deceleration ability (r = -0.54 and -0.55, respectively). All correlations between eccentric KF strength and deceleration ability were unclear. At 180°/s, correlations between eccentric KE strength and deceleration ability were also unclear; however, at 60°/s, both DL (r = -0.63 to -0.64) and NDL (r = -0.54 to -0.55) had very likely large correlations with deceleration ability. These findings provide novel insights into the unilateral KF and KE strength capacities underpinning the ability to decelerate rapidly from high-sprint velocities.